Effects of dl‐3‐n‐butylphthalide on serum lipoprotein‐associated phospholipase A2 and hypersensitive C‐reactive protein levels in acute cerebral infarction - Xiao‐Lei Zhang; Yin‐Tao Dong; Yi Liu; Yi Zhang; Ting‐Ting Li; Feng‐Yun Hu (Brain and Behavior, 2019)
Abstract Objective This study aims to explore the curative effect of dl‐3‐n‐butylphthalide (NBP) on patients with acute cerebral infarction (ACI) and its effects on serum lipoprotein‐associated phospholipase A2 (Lp‐PLA2) and hypersensitive C‐reactive protein (hs‐CRP) levels. Methods A total of 136 ACI patients treated in our hospital, who met the criteria, were selected and randomly divided into two groups: control group (n = 60, including 28 males and 32 females) and treatment group (n = 76, including 32 males and 44 females). Patients in the control group were treated with routine drug therapy, while patients in the treatment group were treated with NBP on this basis. A dose of 100 ml was administered by intravenous injection for 2 times/day, for 14 days. The curative effect was evaluated using the National Institute of Health Stroke Scale (NIHSS) and Barthel index (BI) self‐care ability. The levels of the two factors in serum were measured using enzyme‐linked immunosorbent assay, and the changes in levels of these two factors in serum at different time points before and after treatment were compared between the two groups. Results (a) Lp‐PLA2 and hs‐CRP levels in the treatment group after treatment were significantly lower than those before treatment and those in the control group after treatment (p < .05). (b) The NIHSS and BI scores in the treatment group were significantly lower after treatment than before treatment and those in the control group after treatment (p < .05). Conclusion Dl‐3‐n‐butylphthalide can improve the expression of Lp‐PLA2 and hs‐CRP in serum in ACI patients. Furthermore, NBP has significant efficacy in inhibiting inflammation and improving neurological symptoms.